Burial Practices of the Early European Settlers Through to Today: A Study of Life, Death and the Music In Between - Hall, Justin; Keiley, Maggie (2004)
Colour Written by Robert Chafe & Jillian Keiley. Starring Petrina Bromley, Jennifer Adams, Cheryl Jameson, Susan Kent, Shelley Neville, Anna Stassis Artistic Fraud of Newfoundland Inc.